MINAT SISWA MEMANFAATKAN LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH DITINJAU DARI PERSEPSI SISWA TENTANG LAYANAN KONSELING DAN KONSELOR - Mudjijanti, Fransisca (Widya Warta, 2015)
This study examines the influence ofÂ studentsâ€™ perceptions on counselling servicesÂ and on counselors toward their interestÂ in utilizingÂ the servicesÂ of guidance andÂ counsellingÂ in schools. The sampleÂ of this research is 140 in number. They are the eighth and ninth year students of Catholic Junior High School â€œSt.Â Bernardus Madiunâ€ of 2014/2015. The data collecting made use of questionnaires. The data were analyzed employing multipleÂ linear regression statistical technique. The result of minor hypothesis test applying theÂ t-testÂ showed that there was partial influence of student perceptions onÂ Â counselling servicesÂ andÂ studentÂ perceptionsÂ on counselors toward theÂ students' interestÂ in utilizingÂ the servicesÂ of guidance andÂ counsellingÂ in schools,Â because bothÂ variablesÂ had the valueÂ tÂ calculateÂ >Â  tÂ table (1,960).